2019
DOI: 10.1016/j.neuroimage.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Imaging human cortical responses to intraneural microstimulation using magnetoencephalography

Abstract: The sensation of touch in the glabrous skin of the human hand is conveyed by thousands of fast-conducting mechanoreceptive afferents, which can be categorised into four distinct types. The spiking properties of these afferents in the periphery in response to varied tactile stimuli are well-characterised, but relatively little is known about the spatiotemporal properties of the neural representations of these different receptor types in the human cortex. Here, we use the novel methodological combination of sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…It has been shown in a 7 T fMRI study where participants had both their median nerve stimulated using INMS and their digits mapped using a travelling wave paradigm, that the areas of maximal functional activation occurred within the expected digit area ( Sanchez Panchuelo et al., 2016 ). We have also recently demonstrated that stimulation of a single 1 st order interneuron reliably induces a reduction in neural oscillatory power in S1 in the beta (13–30 ​Hz) band ( O’Neill et al., 2019 ). However, in the latter study we did not have the probabilistic digit maps to corroborate that beta oscillations mapped to the correct digit representations in the cortex.…”
Section: Application Of the Probabilistic Atlas To Electrophysiologicmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown in a 7 T fMRI study where participants had both their median nerve stimulated using INMS and their digits mapped using a travelling wave paradigm, that the areas of maximal functional activation occurred within the expected digit area ( Sanchez Panchuelo et al., 2016 ). We have also recently demonstrated that stimulation of a single 1 st order interneuron reliably induces a reduction in neural oscillatory power in S1 in the beta (13–30 ​Hz) band ( O’Neill et al., 2019 ). However, in the latter study we did not have the probabilistic digit maps to corroborate that beta oscillations mapped to the correct digit representations in the cortex.…”
Section: Application Of the Probabilistic Atlas To Electrophysiologicmentioning
confidence: 97%
“…The datasets and experimental methods have been presented in ( O’Neill et al., 2019 ), and so a summary outline of the data and processing methods follows. In this subset of the data, 3 participants volunteered to undergo INMS of the left median nerve using an in-house microneurography and microstimulation kit ( Glover et al., 2017 ).…”
Section: Application Of the Probabilistic Atlas To Electrophysiologicmentioning
confidence: 99%
“…(2016) and O'Neill et al. (2019) from experimental series B. Commercial tungsten microelectrodes (model UNA15FNM; FHC, Bowdoin, ME, USA) with tip diameters of ∼5 μm were inserted perpendicularly into the skin and adjusted to an intraneural position for neural recordings.…”
Section: Methodsmentioning
confidence: 99%
“…1. The median nerve, which projects to the majority of the glabrous skin of the hand, was accessed ∼3 cm proximal to the wrist; for more details, see Sanchez Panchuelo et al (2016) andO'Neill et al (2019) from experimental series B. Commercial tungsten microelectrodes (model UNA15FNM; FHC, Bowdoin, ME, USA) with tip diameters of ∼5 μm were inserted perpendicularly into the skin and adjusted to an intraneural position for neural recordings.…”
Section: Experimental Approachmentioning
confidence: 99%
“…Our interest was the brain connectivity during the mutual regulation of emotion and movement. According to the literatures (Selma Aybek et al, 2015;Tipper et al, 2015;Hua et al, 2018;Neill et al, 2019), synchronous activation of the frontal lobe and motor cortex occurs during emotion recognition. In the present research, quantitative calculation found similar results in the state of emotion-movement regulation.…”
Section: Motion-affective Connectivitymentioning
confidence: 99%